Canadian Foundation for Refugees Plans Refugee Newsletter - Chenard, E.A. (Refuge: Canada’s Journal on Refugees, 1983)
Above is an excerpt from a letter sent to me by the Canadian Foundation for Refugees. Why is the Foundation planning to produce such a newsletter when Refuge is already being published? Further, the proposed contents of the newsletter overlap ours. This is a waste of government funds. One or the other should not be published. We would like to hear the views of our readers.